Do Innovation Strategies Shape Export Diversification? An Exploration from Middle Income Countries - Ramsha, Saleem; Chin Hong, Puah; Jerome Kueh, Swee Hui; Muhammad Azhar, Bhatti (Macrothink Institute, USA, 2025)
It has been almost three decades that economies are striving for innovations to uplift their production frontier. This study endeavors to find the impact of Technology Choice Index (TCI) and patents to shape the export diversification scenario in sixty five middle income countries for the period 1995-2021. The countries are further segregated in two groups i.e. Upper Middle Income (UMI) and Lower Middle Income (LMI). The employed estimation technique is Method of Moment Quantile Regression (MMQR). The results favour both innovation strategies to affect diversification in exports. Moreover, higher incentives for innovative output and higher productivity for manufacturing produce will have stronger spillover effects upon diversified export frontier. Further, these findings suggest that adopting TCI should be at a balance between risks and benefits attached to it, as policy tool in these countries. The optimal increase in TCI and patents filing will remain a fortifying option for middle income countries to increase export diversification. Future studies need to dig export diversification at country specific sectoral level.